ANALISIS ROOM ATTENDANT DALAM MENERAPKAN STANDAR OPERASIONAL PROSEDUR DI TRAVELODGE BATAM - Devid Simatupang; Eriana Pandiangan (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
This study aims to determine the effectiveness, consistent, and systematic application of standard operational procedure by room attendant at Travelodge Batam. the research uses qualitative methods through a descriptive approach, which describes several data findings that are formulated in the form of words. The tools used to collect data are the results of documentation, observation, and interviews. The results showed from this research that Standard operational procedure have been implemented properly by the room attendant in accordance with three indicators, namely efficient, consistent, and systematic. This is also supported by regular training they do once a week.